Immunovirological response to combined antiretroviral therapy and drug resistance patterns in children: 1- and 2-year outcomes in rural Uganda - Balkan Suna (BMC Pediatrics, 2011)
Abstract Background Children living with HIV continue to be in urgent need of combined antiretroviral therapy (ART). Strategies to scale up and improve pediatric HIV care in resource-poor regions, especially in sub-Saharan Africa, require further research from these settings. We describe treatment outcomes in children treated in rural Uganda after 1 and 2 years of ART start. Methods Cross-sectional assessment of all children treated with ART for 12 (M12) and 24 (M24) months was performed. CD4 counts, HIV RNA levels, antiretroviral resistance patterns, and non-nucleoside reverse transcriptase inhibitor (NNRTI) plasma concentrations were determined. Patient adherence and antiretroviral-related toxicity were assessed. Results Cohort probabilities of retention in care were 0.86 at both M12 and M24. At survey, 71 (83%, M12) and 32 (78%, M24) children remained on therapy, and 84% participated in the survey. At ART start, 39 (45%) were female; median age was 5 years. Median initial CD4 percent was 11% [IQR 9-15] in children < 5 years old (n = 12); CD4 count was 151 cells/mm3 [IQR 38-188] in those ≥ 5 years old (n = 26). At M12, median CD4 gains were 11% [IQR 10-14] in patients < 5 years old, and 206 cells/mm3 [IQR 98-348] in ≥ 5 years old. At M24, median CD4 gains were 11% [IQR 5-17] and 132 cells/mm3 [IQR 87-443], respectively. Viral suppression (< 400 copies/mL) was achieved in 59% (M12) and 33% (M24) of children. Antiretroviral resistance was found in 25% (M12) and 62% (M24) of children. Overall, 29% of patients had subtherapeutic NNRTI plasma concentrations. Conclusions After one year of therapy, satisfactory survival and immunological responses were observed, but nearly 1 in 4 children developed viral resistance and/or subtherapeutic plasma antiretroviral drug levels. Regular weight-adjustment dosing and strategies to reinforce and maintain ART adherence are essential to maximize duration of first-line therapy in children in resource-limited countries.